Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Siswa Mata Pelajaran IPA Kelas IV Madrasah Ibtidaiyah Nurul Hidayah - Usman Roin; Thofa Mustaqim (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Learning activities carried out by teachers in MI Nurul Hidayah have been impressed only by active teachers. The teacher uses more discussion methods during learning, but the discussion is still less effective so students tend to be passive in receiving the subject matter given by the teacher. This study aims to see the effect of Snowball Throwing type cooperative learning models on student learning outcomes in class IV science subjects in Madrasah Ibtidaiyah Nurul Hidayah. The method used in this study is a quantitative experimental method, using primary data collection instruments through tests, and secondary with interviews and observations. The results of this study indicate that hypothesis analysis obtained a T-count value of 3.29 with T-Table 2.00, which means t arithmetic is greater than the t-table which means H0 was rejected and Ha was accepted. The Snowball Throwing type cooperative learning model can have a positive effect on student learning outcomes in class IV science subjects in Madrasah Ibtidaiyah Nurul Hidayah. For this reason, teachers are expected to be able to apply various other types of cooperative learning models in learning, so that students are more active in discussions that can also affect the learning outcomes.